Mesoscale simulation of the mold filling process of Sheet Molding Compound - Meyer, Nils (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2022)
Sheet Molding Compounds (SMC) are discontinuous fiber reinforced composites that are widely applied due to their ability to realize composite parts with long fibers at low cost. A novel Direct Bundle Simulation (DBS) method is proposed in this work to enable a direct simulation at component scale utilizing the observation that fiber bundles often remain in a bundled configuration during SMC compression molding.